Enhancement Performance Of Split Ring Resonator Structure On Microstrip Patch Antenna - Hassan, Nornikman (UTeM, 2016)
Metamaterial is a type of artificial structure that is not found in the nature. This structure has become an interest among many due to its extraordinary response to electromagnetic waves. The split ring resonator is an example of a metamaterial structure, which has the potential to improve the performances of components in microwaves without changing the materials or with additional radiators. First, the possibility to reduce the size of patch antenna while maintaining the acceptable performance at 2.4 GHz with various split ring resonator configurations studied. Next, the ability to produce multi bandwidth performance for Minkowski Island antenna with Minkowski Island split ring resonator had performed. The antenna had designed and simulated with Microwave CST software. Then, the proposed antenna had been fabricated and measured. Meanwhile, the Minkowski Island split ring resonator possessed the ability to reduce the overall physical size of Minkowski patch antenna up to 75.6 % compare with basic rectangular antenna. Then, the Minkowski Island split ring resonator could create multiband resonant frequency at 2.4 GHz, 3.5 GHz, and 5.2 GHz for the Minkowski Island antenna with return loss of - 21.945 dB, - 17.154 dB and - 16.536 dB with gain of 0.874 dB, 1.410 dB and 2.940 dB, respectively. Besides, the resonant frequency could also be controlled by using different combinations size and location of Minkowski Island split ring resonators. The overall size of the antenna still could be maintained although additional split ring resonators were used. Therefore, the multiband system with compact design can be realized to improve the mobility of wireless communication system devices.